2020
DOI: 10.1016/j.ophtha.2019.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Bilateral Cataracts Removed in Infants 1 to 7 Months of Age Using the Toddler Aphakia and Pseudophakia Treatment Study Registry

Abstract: To evaluate outcomes of bilateral cataract surgery in infants 1 to 7 months of age performed by Infant Aphakia Treatment Study (IATS) investigators during IATS recruitment and to compare them with IATS unilateral outcomes.Design: Retrospective case series review at 10 IATS sites.Participants: The Toddler Aphakia and Pseudophakia Study (TAPS) is a registry of children treated by surgeons who participated in the IATS.Methods: Children underwent bilateral cataract surgery with or without intraocular lens (IOL) pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 36 publications
5
88
2
Order By: Relevance
“…This was somewhat inferior to the visual outcome of the Toddler Aphakia and Pseudophakia study (TAPS). 9 However, they excluded most children with chromosomal and neurodevelopmental anomalies from the visual acuity summaries, and the age at surgery was 1 to 7 months. After removing the children with Down syndrome and the one with Lowe syndrome from our study, the median CDVA of the better-seeing eye was comparable to the TAPS study.…”
Section: Discussionmentioning
confidence: 99%
“…This was somewhat inferior to the visual outcome of the Toddler Aphakia and Pseudophakia study (TAPS). 9 However, they excluded most children with chromosomal and neurodevelopmental anomalies from the visual acuity summaries, and the age at surgery was 1 to 7 months. After removing the children with Down syndrome and the one with Lowe syndrome from our study, the median CDVA of the better-seeing eye was comparable to the TAPS study.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype has not been classically associated with PAX6 mutations. Bilateral congenital cataract usually has a good visual prognosis if surgery is performed between 6 and 8 weeks old and no other ocular abnormalities are seen [ 18 ]. Patients with PAX6 mutations often had posterior pole abnormalities such as foveal hypoplasia, which might be difficult to diagnose in a young infant presenting with congenital cataracts, as this patient will characteristically present nystagmus at a low visual acuity, like case 4, 7 and 8.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment Study Registry (TAPS) and the IoLunder2 cohort, demonstrating that GRAE is a common complication threatening visual prognosis after cataract surgery in infants and young children, 3,[23][24][25] with incidence increasing gradually over the postoperative interval. The Infant Aphakia Treatment Study (IATS) reported that the incidence of GRAE in children aged one to six months at the time of cataract extraction rose from 12% at 1 year to 40% at 10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary intraocular lens (IOL) implantation is a common treatment for pediatric aphakia. [1][2][3] In short to mid-term follow-up of 12 to 60 months, the incidence of adverse events (AEs) after IOL implantation in pediatric aphakia has been reported to be as high as 19.5 -28.5%, affecting the prognosis and visual function in these patients. [4][5][6][7][8] In most pediatric aphakic eyes, after cataract extraction, the amount of residual lens capsule is insufficient, or the anterior and posterior capsules of the lens are adherent and scarred, so an IOL can only be implanted in the ciliary sulcus.…”
Section: Introductionmentioning
confidence: 99%